Políticas públicas para a pessoa com deficiência na UFC: a percepção dos alunos com deficiência visual - Sousa, Teana Fátima Brandão de (2014)
By analyzing the historical development of people with disabilities inclusion in higher education, we can observed, by the last Brazilian census, that the enrollments number increased 358% between 2003 and 2011. It is an important data because problematize and raise reflections about this theme. From the 1990’s, was surging some legal documents that gave a support for this students with disabilities and force the IFES to ensure, not only access, but the permanency in the university. We can cite as an example, the Presidential Decree 5.296/2004 and the Ordinance 3.284/2003. Regarding the inclusion of people with disabilities in the Federal University of Ceará (UFC), started by specifics actions and without organization, changing from 2005, with the completion and continuity of the UFC Inclui Project, highlighting the institutionalization of the Accessibility Secretary UFC Inclui. This study, based on qualitative research, aims to know the UFC students with visual disabilities perception about the public policy of inclusion in higher education. To bring to completion this study, some historical clippings were necessary, besides the semi-structured interviews application with seven undergraduate students and one graduate student with visual disabilities. By crossing the results with the research specific objectives, it is possible concluded, from the content analysis (Bardin, 1977), that students have knowledge about the Accessibility Secretary UFC Inclui existence, even consider it essential for them to able to complete their studies each semester. The students also declare that the entrance exam as inclusive, however link that relationship with the teachers are the most committed to studies completion, leading in some cases disciplines failure or even locking them.